2018
DOI: 10.1002/ls.1444
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and tribological properties of chemically decorated MoS2 nanosheets with oleic diethanolamide

Abstract: In this paper, we attempted to modify the self‐made two‐dimensional MoS2 nanosheets by oleic diethanolamide (OD) with a simple one‐step route to obtain OD‐MoS2. The OD‐MoS2 nanosheets were confirmed by a series of characterizations. The results showed that the MoS2 nanosheets could be chemically covered with OD molecules to form CS bond, so as to distinctly improve the dispersibility and stability of OD‐MoS2 nanosheets in base oil. Furthermore, the tribological properties of OD‐MoS2 nanosheets in base oil wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…1,2 For the past decades, nanoparticles have attracted considerable attention as potential oil additives due to their excellent physical and chemical properties. 3 In respect of this, the layered nanoparticles based on strong intraplanar and weak interplanar bonds, such as graphite and its derivatives, 4 hexagonal boron nitride, 5 zirconium phosphates, 6 layered double hydroxides, 7 and transition metal dichalcogenides 8,9 have been recognised as promising alternatives for traditional oil additives. Molybdenum disulfide (MoS 2 ) nanoparticles, as a typical member of transition metal dichalcogenides, are known to enhance the tribological properties of oils in virtue of their excellent frictionreducing and antiwear properties.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 For the past decades, nanoparticles have attracted considerable attention as potential oil additives due to their excellent physical and chemical properties. 3 In respect of this, the layered nanoparticles based on strong intraplanar and weak interplanar bonds, such as graphite and its derivatives, 4 hexagonal boron nitride, 5 zirconium phosphates, 6 layered double hydroxides, 7 and transition metal dichalcogenides 8,9 have been recognised as promising alternatives for traditional oil additives. Molybdenum disulfide (MoS 2 ) nanoparticles, as a typical member of transition metal dichalcogenides, are known to enhance the tribological properties of oils in virtue of their excellent frictionreducing and antiwear properties.…”
Section: Introductionmentioning
confidence: 99%
“…In order, to improve the dispersibility and stability of MoS 2 , Wu et al [100] used oleic diethanolamide (OD) to modify MoS 2 nanosheets, thereafter study the tribological behavior in base-oil using a four-ball tester. The results showed that the average COF and average wear scar diameter of 0.08 wt.% OD-MoS 2 -based oil were reduced by ~36.8% and ~15.4% as compared with the base oil, respectively.…”
Section: Molybdenum Disulfide (Mos 2 )mentioning
confidence: 99%
“…In order, to improve the dispersibility and stability of MoS2, Wu et al [100] used oleic diethanolamide (OD) to modify MoS2 nanosheets, thereafter study the tribological behavior in base-oil using a four-ball tester. The results showed that the average COF and average wear scar diameter of 0.08 wt.% OD-MoS2-based oil were reduced by ~36.8% and ~15.4% as compared with the base oil, respectively.…”
Section: Molybdenum Disulfide (Mos2)mentioning
confidence: 99%